2015
DOI: 10.1080/09540121.2015.1112348
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and parental caregivers as lay health advisers in a community-based risk reduction intervention for youth: baseline data from Teach One, Reach One

Abstract: The purpose of the current study is to describe the demographic, behavioral, and psychosocial characteristics of adolescent and caregiver lay health advisers (LHAs) participating in an intervention designed to reduce risk behaviors among rural African-American adolescents. Teach One, Reach One integrates constructs from the Theory of Planned Behavior and Social Cognitive Theory. It acknowledges that changing the sexual behaviors of African-American adolescents requires changing one's knowledge, attitudes, norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Finally, consistent with findings from Ritchwood et al (2016), it is clear from the data that knowledge about condoms remains an area of concern. A small portion of this sample did not consider condoms to be a form of birth control.…”
Section: Discussionsupporting
confidence: 78%
“…Finally, consistent with findings from Ritchwood et al (2016), it is clear from the data that knowledge about condoms remains an area of concern. A small portion of this sample did not consider condoms to be a form of birth control.…”
Section: Discussionsupporting
confidence: 78%
“…There are a number of interventions aimed at improving PTCS and recent reviews have suggested that those that include caregivers are more effective than those that included either caregivers or youth only (see Akers et al, 2011;Sutton et al, 2014, for review). The Teach One, Reach One intervention, for example, contains both group sessions for caregivers and youth separately, as well as collectively to reinforce training and learning (Dave et al, 2016). More research, however, is needed to determine whether safe sex interventions for rural African American youth that employ caregivers should place emphasis on fostering positive attitudes and building self-efficacy related to PTCS, especially as it relates to sensitive sex topics.…”
Section: Resultsmentioning
confidence: 99%
“…Both caregivers and youth were initially offered $10 each for completing the survey; however, this amount was increased to $30 over the baseline time period to address recruitment challenges experienced in certain counties. Additional details regarding recruitment and training for the intervention study have been reported elsewhere, as the current article focuses only on baseline data (Corbie-Smith et al, 2010;Corbie-Smith et al, 2011;Dave et al, 2016;.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Houve associação entre a vitimização física e psicológica, respectivamente, com a maior escolaridade paterna (ensino médio completo ou mais) e menor escolaridade materna (ensino fundamental incompleto). Pesquisa realizada com adolescentes afro-americanos evidenciou que cuidadores com maior escolaridade e mais esclarecidos sobre as consequências da violência no namoro estimulavam o desenvolvimento de atitudes positivas, relações de namoro saudáveis e baixa aceitação da violência (17) .…”
Section: Discussionunclassified